SIMULATION OF THE CONTACT PROCESS INTERACTIONS OF LAND-MOVING AND EARTH-TRANSPORT MACHINES’ WORKING BODIES WITH FROZEN SOIL - V. N. Kuznetsova; I. S. Kuznetsov (Вестник СибАДИ, 2018)
Introduction. The process of developing frozen soils is considered by the working equipment of earthmoving and earth-moving machinery as a research object. The main aspects of the developed mathematical model and the original method for studying the processes of spatial interaction of the excavating machines’ working bodies with frozen soil are presented. Moreover, such aspects allow to obtain the stress distribution diagrams over the surface of the working body. The nonlinear character of the stresses’ distribution on the contact surface of the working body during the interaction with the soil has been substantiated and proved.Materials and methods. The description and analysis of the experimental results on the coefficients’ quantitative determination, which enter into the mathematical model, and also the boundaries’ establishment of their adequacy are given. The dependencies have been established to determine the experimental coefficients analyticallyResults. The investigations and analysis of the results have been carried out to establish an approximating interrelation between the strength of the frozen soil development and the contact spot on the aluminum plate. Therefore, each abscissa value (the gravity center coordinates of the aluminum plate) and the values of the total normal force are quantified. As a result, good convergence of theoretically obtained dependences with experimental results is shown.Discussion and conclusion. The carried out researches are the basis for the justifying and determining methodology for the working equipment’s optimal parameters of earth-moving machines with increased efficiency by reducing the energy intensity of the developing frozen soils’ process.